1965
DOI: 10.2466/pr0.1965.16.3c.1205
|View full text |Cite
|
Sign up to set email alerts
|

An Automated Apparatus for the Avoidance Training of Rats

Abstract: An apparatus and procedure for the avoidance training of rats is described. 22 rats were trained in the apparatus, and the rapidity of learning was contrasted with that of previously-used automated apparatuses. The new technique prevented many major problems associated with traditional avoidance procedures, both automated and manual.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
40
0

Year Published

1966
1966
1977
1977

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 17 publications
2
40
0
Order By: Relevance
“…The criticisms of shuttle-avoidance training have been that animals learn it slowly (Baum, 1965) and too few learn it at all (Bindra, 1961). Shuttle-avoiding to airblast, however, is not acquired slowly, but four to 30 times faster than electric shock avoidance (Vanderwolf, 1963;Theios, 1963 represent the range of electric shock data).…”
Section: Resultsmentioning
confidence: 99%
“…The criticisms of shuttle-avoidance training have been that animals learn it slowly (Baum, 1965) and too few learn it at all (Bindra, 1961). Shuttle-avoiding to airblast, however, is not acquired slowly, but four to 30 times faster than electric shock avoidance (Vanderwolf, 1963;Theios, 1963 represent the range of electric shock data).…”
Section: Resultsmentioning
confidence: 99%
“…Baum (1970a) was among the first to systematically test methods for deconditioning persisting avoidance. Using rats and an automated one-way avoidance apparatus, Baum (1965Baum ( , 1970a established avoidance, terminated the footshock used to establish the avoidance, and then observed the persistence of avoidance beyond termination of footshock . Between termination of footshock and testing for persistence of avoidance, various treatments were programmed.…”
mentioning
confidence: 99%
“…A direct comparison of these results with those of Baum (1965) is difficult because of differences between the experiments. His animals (rats) were run until they reached a criterion of 10 consecutive avoidances.…”
Section: Resultsmentioning
confidence: 91%
“…In view of the hamster's predilection toward climbing it was felt that the procedure described by Baum (1965) might be useful in obtaining avoidance conditioning. Pilot work indicated that an avoidance response was readily, and rapidly, acquired in this apparatus.…”
mentioning
confidence: 99%